Facile Synthesis of Enantiopure Sugar Alcohols: Asymmetric Hydrogenation and Dynamic Kinetic Resolution Combined. (18th August 2020) - Wang, Jiang; Shao, Pan‐Lin; Lin, Xin; Ma, Baode; Wen, Jialin; Zhang, Xumu
Abstract: An unprecedented Ir/f‐amphox‐catalyzed asymmetric hydrogenation of racemic 2, 3‐ syn ‐dihydroxy‐1, 4‐diones is presented involving dynamic kinetic resolution, which produces (1 R, 2 R, 3 R, 4 R )‐tetraols. This protocol constitutes an efficient and straightforward approach to accessing sugar alcohols bearing four contiguous stereocenters. The strategy exhibits various advantages over existing methods, including excellent yields (up to 98 %), exceptional stereoselectivities (up to 99:1 dr, 99.9 % ee ), operational simplicity and substrate generality. Moreover, the nature of the reaction was revealed as a stepwise transformation by in situ Fourier‐transform infrared spectroscopy and isolation of intermediates. Abstract : An Ir/ f ‐amphox‐catalyzed asymmetric hydrogenation of racemic 2, 3‐ syn ‐dihydroxy‐1, 4‐diones is presented, involving dynamic kinetic resolution to produce 1, 2, 3, 4‐tetraols. This protocol constitutes an efficient and straightforward approach to accessing chiral sugar alcohols. The nature of the reaction was revealed as a stepwise transformation by in situ Fourier‐transform infrared spectroscopy and isolation of intermediates.